Kepemimpinan Camat Dalam Meningkatkan Prestasi Kerja Aparatur Sipil Negara Di Kecamatan Galela Barat - Pola, Herlim; Lengkong, Florence Da; Londa, Very (Sam Ratulangi University, 2017)
Abstract : Study is based on initial observations that the leadership of Camat in improving the performance of the State Civil Apparatus within the government of West Galela District has not been running well. This condition is suspected to have something to do with the lack of optimal decision-making, delegation of authority, supervision, and communication has not been well overnight. This research applies qualitative research method with informant that set as many as 6 people. After the data collected the analysis is done by applying data analysis techniques namely, data reduction, data presentation, and data verification or conclusion.The research shows that (1) In leadership of Camat to improve the performance of Civil State Apparatus apparatus is one of indicator that decision making has not run as expected of Civil State Apparatus in District of Galela Barat. This is because the decision making which is often done by the Camat is not involving the participation of the staff, so there are employees who feel the need for involvement in decision making. (2) Leadership indicators Camat in improving job performance Civil Service Apparatus one of them is the delegation of authority. As per the result of research that indicator have not run well. Due to the reality, there is still less Camat's confidence in subordinates / employees, so that in delegation of authority more in submitted to the Secretary of the Camat in comparison with other employees. (3) One indicator of leadership of Camat that needs to be done is supervision on employee performance. According to the results of the research that the supervisory system Camat on employee performance has not gone well, because seen from the fact that there are still employees who are not disciplined in performing duties as a public servant. (4) As the result of research indicate that communication aspect has been running well, be it communication vertically (Up-Down) or horizontally (Interview).Based on the conclusion above, the researcher suggests that the Camat leadership needs to improve in terms of decision making, delegation of authority, supervision and communication. It is expected that the Camat as the leader to involve the participation of the State Civil Apparatus in the subdistrict of Galela Barat, the delegation of the authority of the Subdistrict Head should see the educational background of the officer who will assume the position temporarily, in order to be able to carry out the tasks according to the instruction of the Camat based on the stated objectives. (3) The sub-district head as the representative of the district government in the kecamatan should further improve the supervisory function on ASN performance. Because in Government Regulation No. 46 of 2011 on the assessment of the performance of civil servants, that one indicator of employee performance is seen from the level of self-discipline employees. By that, the Camat is expected to further tighten supervision in terms of employee discipline in performing duties as a public servant. (4) Communication between leaders and employees can be done better, in order to provide information relating to the duties and functions of each employee in West Galela District.Keywords: Leadership, Camat, Job Performance, State Civil Apparatus